EVALUASI PELAKSANAAN SISTEM INFORMASI MANAJEMENPEMANTAUAN SANITASI TOTAL BERBASIS MASYARAKAT(STBM) PILAR PERTAMA DI KABUPATEN BOYOLALI - PRASETYANINGSIH, ARUM; , Sri Sugiarsi, SKM, M.Kes; , Yuli Kusumawati, SKM., M. Kes (Epid) (2015)
Arum Prasetyaningsih J 410 131 049 To evaluate the performance of information system monitoring total management sanitation community based ( STBM ) the first pillar of the district Boyolali ABSTRACT Of achievement of the program STBM the first pillar the development of the reporting system through SMS gateway and website by the government. Based on preliminary study conducted in Boyolali health department that the use of new SMS gateway start simultaneously by all primary health care in march 2015. The aims of this research is to know the information systems management program monitoring STBM especially the first pillar. Research methodology this uses the method observational with a qualitative approach. The majority of informants interviewed in this research as many as 9 (nine) a person with the methods purposive sampling. The results of the study citing it still found nonconformity the monitoring with the guidebook the arranged ditjen PP and PL. of 2011 such as not disfunction form as a means of monitoring , the frequency of monitoring by sanitarian still diverse , and there are still many sanitarian who do not implement reporting through SMS gateway. Key words: information systems management, surveillance, sanitation total community based (STBM)